Cataract prevalence amongst the elderly community of Rumah Seri Kenangan Cheras, 1994 - Jamaiyah Hj. Haniff; Hanafiah Mohd. Salleh (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
The aim of this study is to see the relationship of cataract and factors like age, sex, ethinicity, level of education, exposure to sunlight, blood pressure, diabetes and habits like smoking and alcohol drinking amongst the elderly community of Rumah Seri Kenangan Cheras. The prevalence of cataract and acceptance of intervention is also studied. This study also looks into the ability of the elderlies in performing several activities of daily living. These information might be useful for health care providers and their policy makers in strategic planning of rehabilitative programmes for them. This cross-sectional study involves 131 of 393 inmates: Instruments include pretested structed questionnaire, blood pressure and visual acquity measurement and funduscopy. Analysis was done with a microcomputer using DBase III and DBstats software. The prevalence obtained was 58 percent. No significant relationship was found between cataract and all the factors studied except for age (p < 0.05). The acceptance towards operative intervention was poor (39.7%) and only 17.1% have been operated. The main reason for not considering operation was not because of ignorence of lvailability and place to seek treatment (1.4%) but because they think that the operation was unnecessary (50.7%), fear (34.7%) and ill health related to age (22.5%). Based on the findings two suggestions are "made. First, considering the high prevalence, elderlies should be routinely screened tor cataract as a treatable cause of blindness. Secondly, they should be motivated to intervention and this may be accomplish through a suitable health education approach.